Respiration rate of fruits and vegetables for modified atmosphere packaging: a mathematical approach - Kandasamy , Palani (Journal of Postharvest Technology, 2024)
Modified atmosphere packaging is a well-proven technology for preserving the natural quality of food products and extending the storage life.  It is one of the most successful preservation techniques suitable for various agricultural and horticultural products. Proper control of  temperature, relative humidity and manipulation of gas composition in storage can successfully extend the shelf life and minimize the extent of  postharvest losses. Respiration is one of the critical elements of the postharvest loss of fresh fruits and vegetables. Modified atmosphere  packaging relies on modifying and controlling the atmosphere inside the storage, achieved by the natural interplay between two processes, the  product's respiration and the transfer of gases through the packaging, leading to an atmosphere richer in CO2 and poorer O2. This  environment can potentially reduce respiration rate, ethylene sensitivity and production, decay, physiological changes and oxidation, thereby  enhancing their shelf-life. Thus, the respiration rate of the selected product is crucial to designing a successful modified atmosphere system. In  this paper, principles of the respiration process, practical methods for measuring respiration rates, factors affecting the respiration rate and  respiratory quotient, modeling the respiration rate and published work on the respiration rate of various fruits and vegetables are discussed.
Keywords: Respiration rate; O2 consumption; CO2 evolution; temperature effect; respiratory kinetics